Representations of Asia in Western Australian Public Library Collections. Issue 1 (2nd January 2021) - White, Hollie; Woods, Denise
ABSTRACT: This research examines Western Australian (WA) public library collections and the representations of Asia in these collections. Serving the needs of the general public within a certain geographic area, public libraries collect materials in all formats and genres based on institutional priorities related to community or user needs and interests. This paper presents findings from a 2019 survey and series of interviews with librarians from WA public libraries to find out more about their collections by examining two types of materials: (1) items about Asia and, (2) items in Asian languages. The key findings are as follows: (1) relatively little attention is paid to cultural representations of the community in the development collections in WA's public libraries (2) LOTE (Languages other than English) materials make up a small percentage of WA public libraries' overall collections; and (3) representations of Asia within the collections are associated thematically with migrant support, travel destinations, cool Asia, and food cultures. This study makes a contribution to research and practice in this area by employing an interdisciplinary approach using cultural studies, library and information studies frameworks, introducing new ways of thinking about these collections and how library materials connect to cultural identity.